Many years of experience of standarding the medium component of wind load on building structures - Pichugin, Sergii; Klochko, Lina (Academic journal Industrial Machine Building Civil Engineering, 2022)
The article contains a systematic review of scientific and technical publications on the problems of wind load for the 90-year period from the 30s of the twentieth century to the present. It is emphasized that this load on the buildings has a complex physical nature and changeable nature. These features are reflected in the sections of design standards of building structures that contain codes of wind load. The main attention is paid to the analysis of the evolution of structural design codes in terms of changes in wind territorial zoning and design factors, the appointment of specified and design values ​​of wind load. It is noted that most of the parameters of wind load codes are probabilistic in nature and require the use of statistical methods to justify them. There is a high scientific level of domestic standards DBN B.1.2-2006 "Loads and loadings", which have a modern probabilistic basis and are associated with Eurocode standards. Scientific results which can be included in the following editions of codes of wind loading are allocated